Penilaian Implementasi e-Government di PUSTEKOM Kemendikbud berbasis metode PEGI - Rahayu, Puji (Universitas Diponegoro, 2017)
According to the Survey UN (United Nations) in 2014, e-government and innovation can provide major opportunities to transform the public administration becomes a tool of sustainable development, provide services more transparent and more accountable. Formerly, the development of government services can be done with a variety of channels, either through online services, big data, social media, mobile applications, or cloud computing, have expanded our perception of e-government services. The research aims to assess the level of achievement of e-Government implementation in the Ministry of Education and Culture of the Republic of Indonesia. Assessment is measured by the Indonesian e-Government Rating framework. The data in this research are obtained by qualitative approach and descriptive data analysis. The finding of this research that the implementation of Â e-Government in Ministry of Education and Culture in the category of